Oral status is associated with chewing difficulty in Thai older adults: data from a National Oral Health Survey - Issarapong Kaewkamnerdpong; Punkanit Harirugsakul; Piyada Prasertsom; Warangkana Vejvithee; Kornkamol Niyomsilp; Orachad Gururatana (BMC, 2023)
Abstract Background The number of older adults in Thailand is increasing. Better chewing ability is associated with healthy aging. Although numerous studies have demonstrated the relationship between social backgrounds, dental service utilization, oral status and chewing difficulty, there is no study in Thailand using national oral health data to identify the variables involved with chewing difficulty among Thai older adults. Therefore, the aim of this study was to determine the association between oral status, and chewing difficulty, adjusting for social backgrounds, and dental service utilization among Thai older adults. Methods This cross-sectional study used data from the eighth Thai National Oral Health Survey (TNOHS). A stratified multi-stage method was used for sample selection. The eighth TNOHS was conducted from June-August 2017. Data were collected using interviews and clinical oral examinations by trained interviewers and trained dentists, respectively. The bivariate analysis, chi-square test was used to explore the associations between social backgrounds, dental service utilization, oral status, and chewing difficulty. Dependent variables with p-values of < 0.2 for their association with independent variables in the bivariate analysis were entered into the multiple logistic regression models. Results This study found that older adults with at least 27 teeth (p < 0.05), or at least eight occlusal pairs (p < 0.05) or income exceeding 15,000 baht per month (p < 0.05) were more likely to have less chewing difficulty (p < 0.001), while the elderly who utilized dental services in the past 12 months were associated with more chewing difficulty than those who did not utilize dental services in the past 12 months (p < 0.001). Conclusions We suggest that policymakers increase the number of preventive plans and set a goal for more than 20 remaining natural teeth and four posterior occlusal pairs in young and working aged people, especially in the low income group.